Analysis of Anisotropy in the Hubble Flow - Torres, Sergio; Cuervo, Juan Carlos (TECCIENCIA, 2018)
An analysis of variations in the Hubble parameter (H0) with line-of-sight direction has been done in order to investigate anisotropy in the motion of the galaxies. Depending on the distance range available in the galaxy sample analyzed, H0 measurements can be used as a probe of intrinsic anisotropies at cosmological scales. At shorter scales, deviations from a smooth Hubble expansion flow are expected when galaxies participate in bulk flow motions towards great attractors. Using a galaxy catalogue that spans the distance range between 45 and 500 Mpc, a statistically robust detection of spatial anisotropy of 6.4 ± 1.4 km s-1 Mpc -1in H0 has been found. Given the limited distance range of the catalogue, this anisotropy could be due to bulk motions.